Characterizing the Saltol quantitative trait locus for salinity tolerance in rice - Thomson, Michael J.; de Ocampo, Marjorie; Egdane, James; Rahman, M. Akhlasur; Sajise, Andres Godwin; Adorada, Dante L.; Tumimbang-Raiz, Ellen; Blumwald, Eduardo; Seraj, Zeba I.; Singh, Rakesh K.; Gregorio, Glenn B.; Ismail, Abdelbagi M. (Springer, 2010)
This study characterized Pokkali-derived quantitative trait loci (QTLs) for seedling stage salinity tolerance in preparation for use in marker-assisted breeding. An analysis of 100 SSR markers on 140 IR29/Pokkali recombinant inbred lines (RILs) confirmed the location of the Saltol QTL on chromosome 1 and identified additional QTLs associated with tolerance. Analysis of a series of backcross lines and near-isogenic lines (NILs) developed to better characterize the effect of the Saltol locus revealed that Saltol mainly acted to control shoot Na+/K+ homeostasis. Multiple QTLs were required to acquire a high level of tolerance. Unexpectedly, multiple Pokkali alleles at Saltol were detected within the RIL population and between backcross lines, and representative lines were compared with seven Pokkali accessions to better characterize this allelic variation. Thus, while the Saltol locus presents a complex scenario, it provides an opportunity for marker-assisted backcrossing to improve salt tolerance of popular varieties followed by targeting multiple loci through QTL pyramiding for areas with higher salt stress.